Alat Inovatif untuk Lean Manufacturing: Meningkatkan Efisiensi dengan PDCA, TRIZ, dan Teknik Bagan Tangan Kanan dan Kiri - Qulub, Irkham Syifaul; Herlambang, Hendi (DPPM UNIVERSITAS PELITA BANGSA, 2024)
This research focused on improving production efficiency in the Lean Manufacturing Laboratory at Universitas Mercu Buana by addressing bottlenecks at the Vacuum and Trimming stations. Utilizing the PDCA methodology, the study aimed to reduce processing times and enhance accuracy through tool design and motion study. The Operational Process Chart identified inefficiencies, while Seven Waste Analysis highlighted key areas for improvement. The application of TRIZ principles led to the development of a flexible cutting press, designed to integrate vacuuming and cutting processes. Measurements using right-hand and left-hand chart facilitated the creation of a new operating procedure. The implementation of the flexible cutting press resulted in a 21.34% reduction in cycle time, demonstrating effective optimization of work layout and tool design. Despite its success, the study has limitations including the lack of a comprehensive cost-benefit analysis and limited product variety. Future research should explore long-term economic impacts and applicability to diverse production contexts.